2020
DOI: 10.1097/cej.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

High mobility group A protein-2 as a tumor cancer diagnostic and prognostic marker: a systematic review and meta-analysis

Abstract: High mobility group A protein-2 (HMGA2) is an architectural transcription factor that binds to the A/T-rich DNA minor groove and is responsible for regulating transcriptional activity of multiple genes indirectly through chromatin change and assembling enhanceosome. HMGA2 is overexpressed in multiple tumor types, suggesting its involvement in cancer initiation and progression, thus, making it an ideal candidate for cancer diagnostic and prognostic. We performed a systematic review to examine the role of HMGA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Typical aberrations in HMGA2 function in cancer are due to overexpression, gene fusion, mutations or truncation (Fusco and Fedele, 2007; Hisaoka et al, 2002; Liu et al, 2020; Young and Narita, 2007). Aberrant HMGA2 re-expression is associated with poor tumor prognosis (Gundlach et al, 2021; Li et al, 2020; Strell et al, 2017; Thi-Hai Pham et al, 2020) and therapy resistance (Dangi-Garimella et al, 2011; Dangi-Garimella et al, 2013; Huldani et al, 2022). Functional studies demonstrated the role of HMGA2 in various aspects of neoplastic transformation (Fedele et al, 2006; Vallone et al, 1997), invasion (Thuault et al, 2006; Watanabe et al, 2009) and metastasis (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Typical aberrations in HMGA2 function in cancer are due to overexpression, gene fusion, mutations or truncation (Fusco and Fedele, 2007; Hisaoka et al, 2002; Liu et al, 2020; Young and Narita, 2007). Aberrant HMGA2 re-expression is associated with poor tumor prognosis (Gundlach et al, 2021; Li et al, 2020; Strell et al, 2017; Thi-Hai Pham et al, 2020) and therapy resistance (Dangi-Garimella et al, 2011; Dangi-Garimella et al, 2013; Huldani et al, 2022). Functional studies demonstrated the role of HMGA2 in various aspects of neoplastic transformation (Fedele et al, 2006; Vallone et al, 1997), invasion (Thuault et al, 2006; Watanabe et al, 2009) and metastasis (Wang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%